2012
DOI: 10.1113/jphysiol.2012.243121
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary nitrate supplementation via beetroot juice on exercising muscle vascular control in rats

Abstract: Key points• Inorganic nitrate (NO 3 − ) supplementation with beetroot juice (BR) in humans lowers blood pressure and the O 2 cost of exercise and may improve exercise tolerance following its reduction to nitrite (NO 2 − ) and nitric oxide (NO).• The effect of inorganic NO 3 − supplementation with BR on skeletal muscle blood flow (BF) and vascular conductance (VC) within and among locomotory muscles during exercise is unknown.• Inorganic NO 3 − supplementation with BR in rats resulted in lower exercising mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
323
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(368 citation statements)
references
References 49 publications
29
323
2
3
Order By: Relevance
“…Hernandez et al, (2012) demonstrated that supplementation with beetroot juice increased force production of the fast twitch muscle fibers of mice which was also associated with an alteration in muscle protein expression. Again using a murine model, Ferguson et al, (2013) also reported that the increase in muscle blood flow following supplementation with beetroot juice only occurred in type II muscle fibers. It is conceivable, therefore, that the blunted response to nitrate supplementation may be attributable to the training status or indeed the muscle fiber type distribution of the participants.…”
Section: Effects Of Nit and Uv-a On Steady-state Exercise And Time Trmentioning
confidence: 94%
See 1 more Smart Citation
“…Hernandez et al, (2012) demonstrated that supplementation with beetroot juice increased force production of the fast twitch muscle fibers of mice which was also associated with an alteration in muscle protein expression. Again using a murine model, Ferguson et al, (2013) also reported that the increase in muscle blood flow following supplementation with beetroot juice only occurred in type II muscle fibers. It is conceivable, therefore, that the blunted response to nitrate supplementation may be attributable to the training status or indeed the muscle fiber type distribution of the participants.…”
Section: Effects Of Nit and Uv-a On Steady-state Exercise And Time Trmentioning
confidence: 94%
“…Evidence from murine models also suggests that increases in muscle blood flow and contractile force production following nitrate supplementation only occur in Type II muscle fibers (Ferguson et al, 2013, Hernandez et al, 2012. One may, therefore, reasonably assume that elite endurance athletes, who are known to have high proportions of type I muscle fibers, would be less likely to benefit from nitrate supplementation (Andersen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate supplementation had no effect on severe-intensity cycling TTE in normoxia, but improved TTE by ~ 8.6 % in hypoxia relative to placebo. Further, there is evidence from murine model investigations that nitrate supplementation may enhance tissue blood flow [41,42] and muscle contractile function [9] preferentially in type II muscle fibres. It is therefore possible that nitrate supplementation is more effective during shorter more high-intensity exercise, during which these muscle fibres are more heavily recruited [9,[43][44][45]64], or else in individuals with greater distribution of type II muscle fibres [43].…”
Section: Effect Of Nitrate Supplementation On Running Performance In mentioning
confidence: 99%
“…Evidence from murine models suggests that the effects of dietary nitrate supplementation may be fibre type specific, increasing muscle perfusion and oxygenation [41,42], and enhancing calcium handling and force production [9] in type II muscle fibres only, as may be recruited during high-intensity exercise (for review, see Jones et al [43]). Moreover, nitrate supplementation has been demonstrated to elicit beneficial effects when the contribution of type II muscle towards force generation is high, including at fast but not slow muscle contraction frequencies [44], and during the transition from moderate to severe but not unloaded to moderate intensity exercise [45].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies in mice have also shown that it can increase 251 muscle force production 21 and increase blood flow to type II muscle fibers 22 . The precise 252 pathway underpinning this ergogenic effect is unclear but the reduction in exercise-induced…”
mentioning
confidence: 99%